The Existence of Aggregate Production Functions - Fisher, Franklin M. (Econometrica, 1969)
This paper discusses recent work on the existence of aggregate production functions in models in which capital goods are specific to firms and cannot be used interchangeably. It is found that this raises problems not only for capital aggregation but also for the existence of labor and output aggregates. Recent work on the question of using aggregate production functions as approximations is also discussed.